2022
DOI: 10.1136/bmjpo-2022-001429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of digital devices and online learning on computer vision syndrome in students during the COVID-19 era: an online questionnaire study

Abstract: PurposeComputer vision syndrome (CVS) describes a group of eye and vision-related problems that result from prolonged digital device use. This study aims to assess the prevalence and associated factors of CVS among students during the lockdown resulting from the COVID-19 pandemic.MethodsA cross-sectional, online, questionnaire-based study performed among high school students in Thailand.ResultsA total of 2476 students, with mean age of 15.52±1.66 years, were included in this study. The mean number of hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
44
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 34 publications
4
44
1
2
Order By: Relevance
“…This rapid increase in screen time can also significantly increase the number of children suffering from CVS. Unfortunately, only limited studies have evaluated the predominance of CVS among school-age children globally, and no study has been conducted in Saudi Arabia [ 16 , 17 , 18 ]. Hence, the main aim of this study was to estimate the prevalence of CVS and its allied risk factors among school-age children during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…This rapid increase in screen time can also significantly increase the number of children suffering from CVS. Unfortunately, only limited studies have evaluated the predominance of CVS among school-age children globally, and no study has been conducted in Saudi Arabia [ 16 , 17 , 18 ]. Hence, the main aim of this study was to estimate the prevalence of CVS and its allied risk factors among school-age children during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of CVS varies from less than 50% to over 90% according to age, occupation, country, and education. [7][8][9][10][11][12][14][15][16][17][18][19]22,30,[35][36][37][38][39] Unfortunately, the COVID-19 pandemic has increased the average daily students' requirements of total screen-hours for online learning and augmented the need for the educational mandated computer system use program. 9,28,30,33,[35][36][37][38][39] Thus, we require more awareness campaigns to increase students' awareness of CVS hazards and protective measures.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][14][15][16][17][18][19]22,30,[35][36][37][38][39] Unfortunately, the COVID-19 pandemic has increased the average daily students' requirements of total screen-hours for online learning and augmented the need for the educational mandated computer system use program. 9,28,30,33,[35][36][37][38][39] Thus, we require more awareness campaigns to increase students' awareness of CVS hazards and protective measures. 9,22,29,31,34,36 Several studies concluded that the unexplained reduction in the visual functions and performances could be attributed to the smartphones and digital screens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations